A study of daylight glare evaluation with prism daylighting redirecting fenestrations. (15th July 2023) - Tian, Zhen; Zhao, Yongqing; Fang, Jiafeng; Kong, Zhe
Abstract: This study explored daylight glare evaluation for Prism Daylight Redirecting Fenestrations (PDRF) with young adults. HDR photography was employed to calculate daylight glare indices, and subjective response was measured by continuous and discrete scales. The statistical results showed that Daylight Glare Probability (DGP) correlated strongly with subjective glare perception and was more robust than Daylight Glare Index (DGI) with PDRF systems. In addition, subjectively estimated glare tolerance time was proposed, and the research results revealed that subjectively estimated glare tolerance time strongly correlated with subjective responses. Vertical eye illuminance as a daylight glare index for PDRF was also investigated. Three Ev thresholds of different glare perception levels were determined based on the confidence intervals analysis. Three Ev values on four categories of perceived glare levels with PDRF for young adults in classrooms under subtropical skies were identified as 2300 lx, 3000 lx, and 4300 lx, corresponding to the thresholds of imperceptible-perceptible, perceptible–disturbing, and disturbing-intolerable, respectively. Graphical abstract: Image 1 Highlights: Glare was evaluated for PDRF which produced unconventional luminance distributions. Field glare rating was obtained from subject's appraisal of the dominant source of glare. A continuous daylight glare scale questionnaire was proposed and utilized. Subjectively estimated glare tolerance time correlated with glare levels was proposed.